Harnessing Interactive Mobile Learning: The Impact of Instagram Reels on German Vocabulary Acquisition - Naqrash, Nadia; Alghazo, Sharif; Al-Momani, Renad; Rayyan, Mohammad (International Journal of Interactive Mobile Technologies (iJIM), 2025)
This study investigates the efficacy of Instagram Reels in supporting vocabulary acquisition by German as a Foreign Language (GFL) students. A mixed-method research design was adopted, utilising quantitative and qualitative measures. A questionnaire was used to examine the use of Instagram Reels by 140 university GFL learners; all were attending courses in GFL at the University of Jordan. Of these, 60 sophomore-level (30 in the control group and 30 in the experimental group) students were recruited to participate in an empirical study to gauge the effect of Instagram-based instruction on German vocabulary acquisition. Pre- and post-tests were administered to measure vocabulary acquisition and use in context. The questionnaire results highlighted that Instagram is a popular tool among GFL learners and that the primary learning goals were academic purposes and personal interests. Participants preferred content focusing on daily language use rather than grammar or cultural aspects. Instagram Reels received positive feedback for improving language skills. The empirical results indicated that the experimental group outperformed the control group; they showed significant improvement in the ability to acquire vocabulary, with adjusted post-test mean scores greater for the experimental group. The study brings to the fore some pedagogical possibilities based on integrating widely used social media tools, in this case, Instagram, while teaching foreign languages. It calls, therefore, for educators to consider a more novel pedagogical approach, creating a more active and interactive environment for learning foreign languages. The study underlines that teaching practices need modification with regard to the changing times and prevailing digital practices that the learners of today’s world have become accustomed to.